Borneolum syntheticum analgesic type scald repair hydrogel material as well as preparation method and application thereof

By coating chitosan on the surface of the borneol and loading it on a modified sodium alginate hydrogel, forming analgesic scald repair hydrogel material, the existing hydrogel dressings are solved by solving the rapid degradation rate and mechanical properties of the existing hydrogel dressings. The problem of good and lack of analgesic effects has achieved efficient wound repair and analgesic effects.

CN119455078APending Publication Date: 2025-02-18XIAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693068.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing hydrogel dressings used for scald wounds, especially sodium alginate hydrogels, have too fast degradation rates, poor mechanical properties, and lack analgesic effects, making it difficult to effectively repair wounds.

Method used

By coating chitosan on the surface of the borneol, the water solubility and bioavailability of the borneol is increased, nanobornae is formed, and it is loaded with gallic acid modified polyvinyl alcohol and 3-aminophenylboric acid modified sodium alginate hydrocoagulation In the glue, a hydrogel material is formed in the analgesic scald repair.

Benefits of technology

The hydrogel material has stable physical and chemical properties, good biocompatibility and high antibacterial efficiency, which can effectively reduce wound pain and promote wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455078A_ABST
    Figure CN119455078A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and discloses a borneol analgesic type scald repair hydrogel material as well as a preparation method and application thereof. The preparation method comprises the following steps: under shielding gas, grafting gallic acid on polyvinyl alcohol to obtain gallic acid modified polyvinyl alcohol; the preparation method comprises the following steps: grafting 3-aminophenylboronic acid onto sodium alginate to obtain 3-aminophenylboronic acid modified sodium alginate; the preparation method comprises the following steps: coating chitosan on the surface of borneol by adopting a micro-emulsion method to obtain a modified nano borneol solution; dissolving gallic acid modified polyvinyl alcohol into the modified nano borneol solution, and uniformly mixing with the 3-aminophenylboronic acid modified sodium alginate solution and the Zn < 2 + > solution for crosslinking to obtain the borneol analgesic scald repair hydrogel material. The preparation method provided by the invention is simple to operate, and the prepared borneol analgesic scald repair hydrogel material integrates multiple functions of analgesia, self-healing, antibiosis and blood vessel formation promotion, and can effectively reduce pain at a wound and promote wound healing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a borneol analgesic scald repair hydrogel material and a preparation method and application thereof. Background Art

[0002] The skin is the largest protective organ on the human body and is easily damaged by physical, chemical and biological factors. Among them, large-area burns caused by physical high temperature or chemical factors are a serious trauma that can cause hundreds of thousands of deaths each year. However, irregular wound shapes and severe bacterial infections make wounds difficult to heal.

[0003] At present, the gold standard for clinical treatment of severe burns is autologous skin transplantation, but this method is limited by limited donors, multiple surgeries and high pain levels for patients. Therefore, the treatment of severe burn wounds is an urgent health problem to be solved in clinical practice.

[0004] In order to solve the above technical problems, reduce the pain of patients, and improve the efficacy of burn wound treatment, researchers and scientists in this field have developed various intelligent multifunctional wound dressings, including films, foams, nanofibers and hydrogels to treat burn wounds. Among them, hydrogels have a unique three-dimensional network structure, which not only highly simulates the extracellular matrix required for cell growth in the body, but also facilitates information exchange between cells and the transfer of nutrients; at the same time, hydrogels have a high water content, can efficiently encapsulate therapeutic substances, and effectively control the release at the lesion site to meet different treatment needs. Therefore, hydrogels are one of the ideal wound dressings for wound healing.

[0005] At present, the hydrogel dressings used for burn wounds in the prior art mainly include sodium alginate hydrogel dressings, but the degradation rate of sodium alginate hydrogel is usually too fast. In order to regulate the degradation rate of sodium alginate hydrogel, additional additives are often required, resulting in a long preparation method and high energy consumption. In addition, the mechanical properties of sodium alginate hydrogel are poor and lack analgesic effect, resulting in the difficulty of effectively repairing wounds when the prepared hydrogel is used as a burn wound repair dressing. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a borneol analgesic burn repair hydrogel material and a preparation method and application thereof.

[0007] The borneol analgesic burn repair hydrogel material of the present invention and its preparation method and application are achieved through the following technical solutions:

[0008] The present invention takes into account that borneol is a traditional Chinese medicine with cooling, analgesic, antibacterial, anti-inflammatory and other effects, but borneol has poor water solubility and low bioavailability, which seriously limits its application in wound healing. In order to improve the water solubility and bioavailability of borneol, so that it can be effectively used for infected scald wounds, the present invention proposes to use chitosan that can respond to the acidic microenvironment of bacterial infection as a modifier of borneol, and under the action of a polyvinyl alcohol emulsifier, a layer of chitosan is coated on the surface of borneol by a microemulsion method to obtain nano borneol, thereby solving the problem of poor water solubility of borneol and improving the bioavailability of borneol. Finally, the nano borneol is loaded in a hydrogel matrix to obtain a borneol analgesic scald repair hydrogel material, so that it can be used as a scald wound repair dressing.

[0009] In order to provide a hydrogel matrix with stable physicochemical properties, good biocompatibility and high antibacterial efficiency, so that the above-mentioned loaded drugs can stably exert their analgesic effect in the hydrogel material, and then can be used as an analgesic burn wound repair dressing, the present invention proposes to use gallic acid-modified polyvinyl alcohol and 3-aminophenylboronic acid-modified sodium alginate as the raw materials for preparing the hydrogel, and in the presence of Zn 2+ Under the action of the gallic acid modified polyvinyl alcohol and the sodium alginate modified by 3-aminophenylboronic acid can cross-link to form a self-repairing dynamic covalent bond hydrogel, that is, a hydrogel with self-healing function. However, the present invention found in the process of exploration that the degree of cross-linking of dynamic covalent bonds or physical non-covalent bonds affects the mechanical strength and self-healing efficiency of the hydrogel. Therefore, the present invention proposes to adjust the ratio between gallic acid modified polyvinyl alcohol and 3-aminophenylboronic acid modified sodium alginate to achieve the mechanical strength and self-healing ability of the hydrogel matrix, so as to achieve the effect that the hydrogel can adapt to dynamic irregular burn wounds, and obtain a borneol analgesic burn repair hydrogel material. And the preparation method of the borneol analgesic burn repair hydrogel material of the present invention specifically includes the following steps:

[0010] Step 1, functionalization treatment of polyvinyl alcohol:

[0011] In a protective gas atmosphere, gallic acid is grafted onto polyvinyl alcohol through an esterification reaction under the action of a catalyst to obtain gallic acid-modified polyvinyl alcohol.

[0012] It should be noted that the present invention uses gallic acid as the functional group of polyvinyl alcohol, and reacts under the action of a catalyst, and the carboxyl group of the gallic acid reacts with the hydroxyl group of the polyvinyl alcohol to undergo an esterification reaction, thereby achieving the grafting of gallic acid onto polyvinyl alcohol, and further achieving the functionalization treatment of polyvinyl alcohol by gallic acid. Since gallic acid has a polyphenol structure, the gallic acid-modified polyvinyl alcohol obtained by the present invention has good antioxidant, adhesive and antibacterial properties. In addition, gallic acid can react with Zn by chelation. 2+The bioactive metal ions such as Zn 2+ Metal ions such as these further enhance the antibacterial properties of the hydrogel material and its ability to promote angiogenesis due to their special biological activity, thereby accelerating the healing of burn wounds.

[0013] In some preferred embodiments of the present invention, the structural formula of the gallic acid-modified polyvinyl alcohol is as shown in Formula 1:

[0014]

[0015] In some preferred embodiments of the present invention, the mass ratio of gallic acid to polyvinyl alcohol is 1 to 2:1, so as to ensure that the functionalization treatment of polyvinyl alcohol can be achieved by the added gallic acid.

[0016] In some preferred embodiments of the present invention, the catalyst is 4-dimethylaminopyridine, so that the catalyst promotes the bonding reaction between the carboxyl group of gallic acid and the hydroxyl group of polyvinyl alcohol.

[0017] In some preferred embodiments of the present invention, the mass ratio of the catalyst to the polyvinyl alcohol is 5 to 8:1, so as to ensure that the added catalyst can graft gallic acid onto the polyvinyl alcohol through an esterification reaction.

[0018] In some preferred embodiments of the present invention, the reaction temperature of the esterification reaction is 70° C., and the reaction time is 36 h to 60 h.

[0019] In some preferred embodiments of the present invention, the catalyst is first dissolved in water to form a solution, and then added to the mixture of polyvinyl alcohol and gallic acid under a protective gas atmosphere to improve the esterification reaction efficiency of polyvinyl alcohol and gallic acid. In some more preferred embodiments of the present invention, the concentration of the catalyst solution is 0.11 g / mL to 0.12 g / mL.

[0020] In some preferred embodiments of the present invention, before adding the catalyst solution, polyvinyl alcohol is first dissolved in water to form a polyvinyl alcohol solution, and then gallic acid is added to the polyvinyl alcohol solution in powder form and mixed, and then the catalyst solution is added under a protective gas atmosphere to ensure that the esterification reaction of gallic acid and polyvinyl alcohol is fully carried out. The polyvinyl alcohol solution is prepared by mixing polyvinyl alcohol and water in a dosage ratio of 0.25g:10mL~20mL.

[0021] In some preferred embodiments of the present invention, the protective gas atmosphere used is N2 atmosphere to avoid oxidation of gallic acid, while allowing the esterification reaction of gallic acid and polyvinyl alcohol to proceed efficiently and safely.

[0022] Since the reaction is carried out in a solution system and the final product is also present in the solution system, the present invention also performs the following post-treatment on the reaction solution after the reaction: collect the reaction solution after the reaction, perform dialysis treatment, and obtain a dialysate. The obtained dialysate is freeze-dried to obtain the gallic acid-modified polyvinyl alcohol. Wherein, in some preferred embodiments of the present invention, when performing dialysis, the collected reaction solution is placed in a dialysis bag with a molecular weight cutoff of 14,000, and the dialysis treatment is performed for 2 to 4 days to obtain a dialysate. In some preferred embodiments of the present invention, the process conditions of freeze drying are: -65°C to -55°C, vacuum degree ≤1kPa, drying time of 48h to 72h, and the product after freeze drying is solid gallic acid-modified polyvinyl alcohol.

[0023] Step 2, modification of sodium alginate:

[0024] In a 2-morpholineethanesulfonic acid buffer solution with a pH value of 4 to 7, 3-aminophenylboronic acid is grafted onto sodium alginate under the action of an activator to obtain 3-aminophenylboronic acid modified sodium alginate.

[0025] It should be noted that the present invention uses 3-aminophenylboronic acid as a modifier for the natural biodegradable polymer sodium alginate. Sodium alginate can also react with Zn 2+ The metal ions such as zinc oxide chelate and form a hydrogel network, which can synergize with the gallic acid in the gallic acid-modified polyvinyl alcohol to further improve the Zn 2+ The chelation of metal ions such as zinc ions and zinc ions is further carried out by cross-linking the hydroxyl groups on the gallic acid-modified polyvinyl alcohol and the boric acid groups on the 3-aminophenylboronic acid-modified sodium alginate through dynamic borate ester bonds to form a hydrogel network structure. 2+ The metal ions are chelated to form a second hydrogel network structure, so that the hydrogel material of the present invention has a multiple cross-linking mechanism.

[0026] In some preferred embodiments of the present invention, the 3-aminophenylboronic acid modified sodium alginate has a structural formula as follows:

[0027] As shown in formula 2:

[0028]

[0029] In some preferred embodiments of the present invention, the mass ratio of 3-aminophenylboronic acid to sodium alginate is 0.6-1:1, so as to achieve the modification effect of 3-aminophenylboronic acid on sodium alginate, thereby obtaining 3-aminophenylboronic acid modified sodium alginate. More preferably, it is 0.6-0.8:1.

[0030] In some preferred embodiments of the present invention, the activator is one or more of methylmorpholine hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide, so that the activator used can activate the carboxyl group.

[0031] In some preferred embodiments of the present invention, the mass ratio of the activator to the 3-aminophenylboronic acid is 4 to 5:1, so as to ensure that the added activator can activate the carboxyl group.

[0032] In some preferred embodiments of the present invention, the reaction temperature of the amidation reaction is room temperature, and the reaction time is 36 h to 60 h.

[0033] It should also be noted that in the 2-morpholineethanesulfonic acid buffer used in the present invention, the English name of 2-morpholineethanesulfonic acid is 2-(4-MorpHolino)ethanesulfonic acid, referred to as MES, so 2-morpholineethanesulfonic acid buffer is also called MES buffer. In some preferred embodiments of the present invention, the 3-aminophenylboronic acid modified sodium alginate is realized by the following steps: first dissolving sodium alginate in MES buffer to form a sodium alginate solution; then, adding an activator to mix, so as to activate the carboxyl group in sodium alginate by the activator; finally, adding 3-aminophenylboric acid to mix, so that the carboxyl group of the sodium alginate and the amino group of 3-aminophenylboric acid undergo amidation reaction, and then realize grafting 3-aminophenylboric acid to sodium alginate, and obtain 3-aminophenylboric acid modified sodium alginate. Wherein, in some more preferred embodiments of the present invention, the sodium alginate solution is prepared by mixing sodium alginate and MES buffer in a ratio of 0.5g:25mL~35mL.

[0034] In some more preferred embodiments of the present invention, the pH of the MES buffer is 4-7, and the concentration is 45mM-55mM.

[0035] The present invention takes into account that since the amidation reaction is carried out in a solution system, the final product is also present in the solution system, so the present invention also performs the following post-treatment on the reaction solution after the amidation reaction: collect the reaction solution after the amidation reaction, perform dialysis treatment, and obtain a dialysate. The obtained dialysate is freeze-dried to obtain the 3-aminophenylboronic acid modified sodium alginate. Among them, in some preferred embodiments of the present invention, when performing dialysis, the collected reaction solution after the amidation reaction is placed in a dialysis bag with a molecular weight cutoff of 14000, and the dialysis treatment is performed for 2 to 4 days to obtain a dialysate. In some preferred embodiments of the present invention, the process conditions of freeze drying are: -65°C to -55°C, vacuum degree ≤1kPa, drying time is 48h to 72h, and the product after freeze drying is solid 3-aminophenylboronic acid modified sodium alginate.

[0036] Step 3, modification of borneol:

[0037] The chitosan was coated on the surface of borneol by microemulsion method to obtain modified nano-borneol solution.

[0038] It should be noted that, in some preferred embodiments of the present invention, chitosan is coated on the surface of borneol to obtain a modified nano-borneol solution by the following steps: borneol is dispersed in an organic solvent to obtain a borneol solution; chitosan is dispersed in acetic acid, and then, under the action of an emulsifier, polyvinyl alcohol, the borneol solution is added and mixed to coat the chitosan on the surface of the borneol to obtain an emulsion; the emulsion is stirred at room temperature to evaporate the organic solvent in the emulsion to obtain a transparent solution, and the obtained transparent solution is the modified nano-borneol solution.

[0039] Among them, in some more preferred embodiments of the present invention, the mass ratio of the borneol to the chitosan is 1:2-14.

[0040] In some more preferred embodiments of the present invention, the added amount of the emulsifier polyvinyl alcohol is 5% to 10% of the borneol solution.

[0041] In some more preferred embodiments of the present invention, the ratio of chitosan to acetic acid is 0.02 g to 0.07 g: 5 mL, wherein the mass concentration of acetic acid is 2.5% to 3.5%.

[0042] In some more preferred embodiments of the present invention, the concentration of the borneol solution is 90 mg / mL to 110 mg / mL. Wherein, the organic solvent is CH2Cl2.

[0043] In some more preferred embodiments of the present invention, the volume ratio of the chitosan solution to the borneol solution is 5 mL:45 μL-55 μL.

[0044] In some more preferred embodiments of the present invention, when the emulsion is stirred, the stirring rate is 800 rpm to 1000 rpm.

[0045] Step 4, cross-linking treatment:

[0046] The gallic acid modified polyvinyl alcohol is dissolved in the modified nano borneol solution to obtain a gallic acid modified polyvinyl alcohol solution; the 3-aminophenylboric acid modified sodium alginate is dispersed in water to obtain a 3-aminophenylboric acid modified sodium alginate solution; the gallic acid modified polyvinyl alcohol solution, the 3-aminophenylboric acid modified sodium alginate solution and Zn 2+ The solution is mixed evenly to allow each component to fully contact and cross-link, thereby obtaining the borneol analgesic burn repair hydrogel material.

[0047] It should be noted that the present invention comprises the gallic acid modified polyvinyl alcohol solution, the 3-aminophenylboronic acid modified sodium alginate solution, the modified nano borneol solution and Zn 2+ The solutions are fully mixed at a certain volume ratio, and a dynamic borate ester bond is formed between the hydroxyl groups on the gallic acid-modified polyvinyl alcohol and the boric acid groups on the 3-aminophenylboronic acid-modified sodium alginate; at the same time, the Zn 2+ Zn in solution 2+ Coordinated with polyphenolic structures on gallic acid-modified polyvinyl alcohol; Zn 2 + Zn in solution 2+ Ionic bonds between the carboxylate ions on the 3-aminophenylboronic acid modified sodium alginate; hydrogen bonds between the boronic acid functionalized polyvinyl alcohol and the 3-aminophenylboronic acid modified sodium alginate form a self-healing hydrogel matrix with multiple cross-linking mechanisms. Moreover, while forming the self-healing hydrogel matrix, the loaded drug-modified nano-borneol is evenly distributed in the self-healing hydrogel matrix, and a borneol analgesic scald repair hydrogel material with multiple functions of analgesia, self-healing, antibacterial and angiogenesis is obtained, so that the borneol analgesic scald repair hydrogel material of the present invention can effectively reduce the pain at the wound and promote wound healing. And the borneol analgesic scald repair hydrogel material of the present invention has a triple physical and chemical cross-linking effect of dynamic borate ester bonds, metal coordination bonds and hydrogen bonds. Compared with the hydrogel matrix formed by a single cross-linking mechanism, the mechanical strength of the borneol analgesic scald repair hydrogel material of the present invention can be flexibly regulated and the biological activity is significantly enhanced.

[0048] In some more preferred embodiments of the present invention, the gallic acid-modified polyvinyl alcohol, the 3-aminophenylboronic acid-modified sodium alginate and Zn 2+ The volume ratio of the solution is 1-2:3-10:1-3.

[0049] In some more preferred embodiments of the present invention, the Zn 2+ The concentration of the solution is 0.08mol / L~0.12mol / L.

[0050] In some more preferred embodiments of the present invention, the mass concentration of the modified nano-borneol solution is 0.8 mg / mL to 1.2 mg / mL; and the mass concentration of gallic acid-modified polyvinyl alcohol in the gallic acid-modified polyvinyl alcohol solution is 18 wt % to 22 wt %.

[0051] In some more preferred embodiments of the present invention, the mass concentration of the 3-aminophenylboronic acid modified sodium alginate solution is 0.5wt% to 1wt%.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] The invention uses gallic acid as a modifier of polyvinyl alcohol. Under a protective gas atmosphere, the carboxyl group of gallic acid and the hydroxyl group of polyvinyl alcohol are esterified under the action of a catalyst to graft gallic acid onto polyvinyl alcohol, thereby functionalizing polyvinyl alcohol through gallic acid. Since gallic acid has a polyphenol structure, the modification of gallic acid in the polyvinyl alcohol chain can increase the antibacterial property, antioxidant property and adhesion property of polyvinyl alcohol, thereby enriching the biological function of polyvinyl alcohol, and obtaining gallic acid-modified polyvinyl alcohol.

[0054] The invention uses 3-aminophenylboronic acid as a modifier of sodium alginate, a natural biodegradable polymer, and activates the carboxyl group of sodium alginate by an activator, so that the carboxyl group of the sodium alginate and the amino group of the 3-aminophenylboronic acid undergo an amidation reaction, thereby achieving the grafting of 3-aminophenylboronic acid onto the sodium alginate, and obtaining 3-aminophenylboronic acid modified sodium alginate.

[0055] The present invention uses pH-responsive chitosan as a modifier for borneol, and obtains pH-responsive modified nano-borneol by coating a layer of chitosan on the surface of borneol, thereby improving the water solubility and bioavailability of borneol. The present invention uses modified nano-borneol as a loaded drug, and combines it with gallic acid-modified polyvinyl alcohol, 3-aminophenylboronic acid-modified sodium alginate and Zn 2+ The solution is mixed, and due to the presence of a large number of hydroxyl groups on the gallic acid-modified polyvinyl alcohol and the presence of boric acid groups on the 3-aminophenylboronic acid-modified sodium alginate, a dynamic borate ester bond can be formed between the gallic acid-modified polyvinyl alcohol and the 3-aminophenylboronic acid-modified sodium alginate to achieve cross-linking. 2+ Zn in solution 2+ Gallic acid modified polyvinyl alcohol (Zn 2+ Coordinated with polyphenol structure) and 3-aminophenylboronic acid modified sodium alginate (Zn 2+ The ionic bonds and hydrogen bonds between the borneol and carboxylate ions form a self-healing hydrogel matrix with multiple cross-linking mechanisms; and while forming the self-healing hydrogel matrix, the loaded drug-modified nano-borneol is evenly distributed in the self-healing hydrogel matrix, so that the borneol analgesic scald repair hydrogel material with multiple functions of analgesia, self-healing, antibacterial and angiogenesis promotion is obtained, so that the borneol analgesic scald repair hydrogel material of the present invention can effectively reduce the pain at the wound and promote wound healing. And the borneol analgesic scald repair hydrogel material of the present invention has a triple physical and chemical cross-linking effect of dynamic borate ester bond, metal coordination bond and hydrogen bond. Compared with the hydrogel matrix formed by a single cross-linking mechanism, the mechanical strength of the borneol analgesic scald repair hydrogel material of the present invention can be flexibly regulated and the biological activity is significantly enhanced.

[0056] The borneol analgesic scald repair hydrogel material prepared by the present invention exhibits good analgesic effect, self-healing performance, adhesion, biocompatibility and antibacterial properties, and effectively promotes wound repair.

[0057] The gallic acid used in the present invention has a polyphenol structure. The modification of gallic acid in the polyvinyl alcohol chain can increase the antibacterial, antioxidant and adhesive properties of polyvinyl alcohol. Gallic acid can react with Mg through chelation. 2+ or Zn 2+ Metal ions such as Zn 2+ The metal ions also have key biological functions, mainly including antimicrobial properties and the role of promoting angiogenesis, thereby accelerating wound healing.

[0058] The sodium alginate in the present invention is a natural biodegradable polymer that can react with Ca 2+ 、Zn 2+ and Sr 2+ The metal ions are chelated and form a hydrogel network.

[0059] The dynamic borate ester bonds, metal coordination bonds and hydrogen bonds formed in the present invention allow for flexible regulation of the mechanical strength of the PGSB hydrogel.

[0060] In terms of self-healing performance, the borneol analgesic scald repair hydrogel material prepared by the present invention can automatically repair to its original state after breaking; in terms of analgesia, the borneol analgesic scald repair hydrogel material prepared by the present invention can effectively reduce the pain of mice; in terms of biocompatibility, the borneol analgesic scald repair hydrogel material prepared by the present invention has good cell compatibility, and the hemolysis rate is less than 5%; in terms of adhesion, the borneol analgesic scald repair hydrogel material prepared by the present invention can adhere to various substrates; in terms of antibacterial performance, the borneol analgesic scald repair hydrogel material prepared by the present invention has good bactericidal ability, and can kill more than 99% of Staphylococcus aureus and Escherichia coli. Based on the above, it can be seen that the borneol analgesic scald repair hydrogel material prepared by the present invention has good self-healing performance, analgesia, biocompatibility, adhesion and antibacterial properties, which lays a foundation for the application of hydrogel in the field of scald wound repair and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of the preparation process of borneol analgesic burn repair hydrogel material.

[0062] Figure 2It is the nuclear magnetic resonance hydrogen spectrum of the gallic acid modified polyvinyl alcohol and 3-aminophenylboronic acid modified sodium alginate polymer in Example 1; wherein, Figure A is the nuclear magnetic resonance hydrogen spectrum of 3-aminophenylboronic acid modified sodium alginate prepared in Example 1, and Figure B is the nuclear magnetic resonance hydrogen spectrum of the gallic acid modified polyvinyl alcohol prepared in Example 1.

[0063] Figure 3 It is the numerical change of storage modulus and loss modulus of PGSB of Example 1 and PGS of Comparative Example 1, wherein G' is the storage modulus of the hydrogel, and G" is the loss modulus of the hydrogel.

[0064] Figure 4 The macroscopic morphological changes during the self-healing behavior of PGSB in Example 1.

[0065] Figure 5 Figures 2 show the adhesion test results of PGSB hydrogel to different substrates, where (a) shows the adhesion test results of PGSB hydrogel to 5mL glass bottle, (b) shows the adhesion test results of PGSB hydrogel to 20mL glass bottle, (c) shows the adhesion test results of PGSB hydrogel to 5mL plastic centrifuge tube, (d) shows the adhesion test results of PGSB hydrogel to 50mL plastic centrifuge tube, (e) shows the adhesion test results of PGSB hydrogel to 20g wood block, (f) shows the adhesion test results of PGSB hydrogel to 20g metal weight, and (g) shows the adhesion test results of PGSB hydrogel to 50g metal weight.

[0066] Figure 6 Figures 2 and 3 show the adhesion test results of PGSB hydrogel to organic tissue substrates, wherein (a) shows the adhesion test results of PGSB hydrogel to mouse kidney, (b) shows the adhesion test results of PGSB hydrogel to mouse spleen, (c) shows the adhesion test results of PGSB hydrogel to mouse heart, (d) shows the adhesion test results of PGSB hydrogel to mouse liver, and (e) shows the adhesion test results of PGSB hydrogel to mouse lung.

[0067] Figure 7 The results of fluorescence microscopy cell morphology test after Live / Dead staining of PGSB of Example 1 and PGS of Comparative Example 1.

[0068] Figure 8 The cell viability test results of PGSB in Example 1 and PGS in Comparative Example 1 are shown.

[0069] Fig. 9Schematic diagram of the antibacterial effect of PGSB of Example 1 and PGS of Comparative Example 1; wherein (a) is a schematic diagram of an Escherichia coli culture medium plate, and (b) is a schematic diagram of a Staphylococcus aureus culture medium plate.

[0070] Fig.10 The antibacterial rates of PGSB in Example 1 and PGS in Comparative Example 1 against Escherichia coli.

[0071] Fig.11 The antibacterial rates of PGSB in Example 1 and PGS in Comparative Example 1 against Staphylococcus aureus.

[0072] Fig.12 Schematic diagram of the time-dependent morphological repair effect of burn wounds in mice after treatment with PGS and PGSB hydrogels.

[0073] Fig.13 This is a graph showing the changes in the size of burn wounds in mice over time after treatment with PGS and PGSB hydrogels.

[0074] Fig.14 This is a schematic diagram of the facial expression index of mice 0, 3, 7, and 14 days after scald treatment. DETAILED DESCRIPTION

[0075] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0076] Example 1

[0077] This embodiment provides a borneol analgesic burn repair hydrogel material, and the hydrogel material is Figure 1 The steps shown yield:

[0078] Step 1, functionalization treatment of polyvinyl alcohol:

[0079] 1.1) Using 4-dimethylaminopyridine as a catalyst, 0.35 g of 4-dimethylaminopyridine was dissolved in 3 mL of distilled water to obtain a catalyst solution.

[0080] 1.2) Dissolve 0.25 g of polyvinyl alcohol in 15 mL of distilled water to obtain a polyvinyl alcohol solution.

[0081] 1.3) Add 0.48 g of gallic acid powder to the polyvinyl alcohol solution of 1.2) and mix well. Then, under a N2 atmosphere, dropwise add the catalyst solution of 1.1) to obtain a mixed solution.

[0082] 1.4) The mixed solution of 1.3) was reacted at room temperature for 48 hours.

[0083] 1.5) The reaction solution after the polymerization reaction in 1.4) was collected and placed in a dialysis bag with a molecular weight cutoff of 14,000, and dialyzed for 3 days to obtain a dialysate.

[0084] 1.6) The dialysate prepared in 1.5) was freeze-dried at -60°C for 72 h to obtain a brown solid, which was gallic acid-modified polyvinyl alcohol, denoted as PVA-GA, which was stored in a vacuum desiccator for later use.

[0085] Step 2, modification of sodium alginate:

[0086] 2.1) Dissolve 0.5 g of sodium alginate in 30 mL of distilled water to obtain a sodium alginate solution.

[0087] 2.2) Add 50 mL of MES buffer with a pH of 6 and a concentration of 50 mM to the sodium alginate solution of 2.1) above to dilute it to obtain a diluted sodium alginate solution.

[0088] 2.3) Using methylmorpholine hydrochloride as an activator, 0.7 g of methylmorpholine hydrochloride was added to the sodium alginate diluted solution in 2.2) and mixed well, and then 0.34 g of 3-aminophenylboronic acid was added and mixed well to obtain a mixed solution.

[0089] 2.4) The mixed solution of 2.3) was reacted at room temperature for 48 hours.

[0090] 2.5) The reaction solution after the reaction in 2.4) was collected and placed in a dialysis bag with a molecular weight cutoff of 14,000, and dialyzed for 3 days to obtain a dialysate.

[0091] 2.6) The dialysate of 2.5) was freeze-dried at -60°C for 72 hours to obtain a solid product, namely 3-aminophenylboronic acid modified sodium alginate, denoted as SA-PBA.

[0092] Step 3, modification of borneol:

[0093] 3.1) Acetic acid and distilled water are prepared to form an acetic acid solution with an acetic acid mass concentration of 3%, and then polyvinyl alcohol is mixed with the acetic acid solution obtained above to prepare a polyvinyl alcohol solution with a polyvinyl alcohol mass concentration of 5%; then 5 mL of the above polyvinyl alcohol solution with a mass concentration of 5% is mixed with 0.05 g of chitosan to obtain a chitosan solution.

[0094] 3.2) Disperse borneol in CH2Cl2 solvent to obtain a borneol solution with a concentration of 100 mg / mL.

[0095] 3.3) Add 50 μL of the borneol solution of 3.2) to the chitosan solution of 3.1) and mix well to obtain an emulsion.

[0096] 3.4) The emulsion of 3.3) was stirred at room temperature at a stirring rate of 900 rpm for 19 h to evaporate the CH2Cl2 solvent, thereby obtaining a transparent modified nano-borneol solution with a concentration of 1 mg / mL.

[0097] Step 4, cross-linking treatment:

[0098] 4.1) Dissolve ZnSO4 in distilled water to prepare a 0.1 M ZnSO4 solution.

[0099] 4.2) Dissolving gallic acid-modified polyvinyl alcohol in the modified nano-borneol solution to prepare a gallic acid-modified polyvinyl alcohol solution with a mass concentration of 20%.

[0100] 4.3) Dissolve 3-aminophenylboronic acid modified sodium alginate in distilled water to prepare a 3-aminophenylboronic acid modified sodium alginate solution with a mass concentration of 0.75%.

[0101] 4.4) At room temperature, the ZnSO4 solution, gallic acid-modified polyvinyl alcohol solution and 3-aminophenylboronic acid-modified sodium alginate solution obtained in 4.1)-4.3) above are mixed in a volume ratio of 5:20:50 to obtain a borneol analgesic burn repair hydrogel material. The borneol analgesic burn repair hydrogel material of this embodiment is recorded as PGSB.

[0102] Comparative Example 1

[0103] The difference between this comparative example and Example 1 is only that:

[0104] In this comparative example, the modified nano-borneol solution used to dissolve gallic acid-modified polyvinyl alcohol was replaced with a corresponding volume of distilled water, that is, no modified nano-borneol solution was added in this comparative example.

[0105] The hydrogel material of this comparative example is recorded as PGS.

[0106] Example 2

[0107] This embodiment provides a borneol analgesic burn repair hydrogel material, and the difference between this embodiment and embodiment 1 is that:

[0108] In 1.1) of this embodiment, the mass of 4-dimethylaminopyridine is 0.4 g.

[0109] In 1.1) of this embodiment, the mass of the phytochemical powder is 0.5 g.

[0110] In 2.2) of this example, the pH of the MES buffer solution is 5.

[0111] In 2.4) of this embodiment, the reaction time is 36 h.

[0112] In 3.1) of this embodiment, the mass of chitosan is 0.02 g.

[0113] In 4.4) of this embodiment, the volume ratio of the ZnSO4 solution, the gallic acid-modified polyvinyl alcohol solution and the 3-aminophenylboronic acid-modified sodium alginate solution is 10:15:20.

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 2 is only that:

[0116] In this comparative example, no borneol was added, and the gallic acid-modified polyvinyl alcohol was dissolved in distilled water.

[0117] Example 3

[0118] This embodiment provides a borneol analgesic burn repair hydrogel material. The difference between this embodiment and embodiment 1 is that:

[0119] In 1.1) of this embodiment, the mass of 4-dimethylaminopyridine is 0.3 g.

[0120] In 1.3) of this embodiment, the mass of gallic acid powder is 0.4 g.

[0121] In 2.2) of this example, the pH of the MES buffer solution is 7.

[0122] In 2.3) of this embodiment, the mass of methylmorpholine hydrochloride is 0.6 g.

[0123] In 3.1) of this embodiment, the mass of chitosan is 0.04 g.

[0124] In 3.4) of this embodiment, the concentration of the modified nano-borneol solution is 0.8 mg / mL.

[0125] In 4.4) of this embodiment, the volume ratio of the ZnSO4 solution, the gallic acid-modified polyvinyl alcohol solution and the 3-aminophenylboronic acid-modified sodium alginate solution is 5:10:20.

[0126] Comparative Example 3

[0127] The difference between this comparative example and Example 3 is only that:

[0128] In this comparative example, no borneol was added, and the gallic acid-modified polyvinyl alcohol was dissolved in distilled water.

[0129] Example 4

[0130] This embodiment provides a borneol analgesic burn repair hydrogel material. The difference between this embodiment and embodiment 1 is that:

[0131] In 1.1) of this embodiment, the mass of 4-dimethylaminopyridine is 0.25 g.

[0132] In 1.3) of this embodiment, the mass of gallic acid powder is 0.45 g.

[0133] In 2.2) of this example, the pH of the MES buffer solution is 4.

[0134] In 2.3) of this example, the amount of methylmorpholine hydrochloride is 0.75 g.

[0135] In 2.4) of this embodiment, the reaction time is 60h.

[0136] In 3.1) of this embodiment, the mass of chitosan is 0.06 g.

[0137] In 4.4) of this embodiment, the volume ratio of the ZnSO4 solution, the gallic acid-modified polyvinyl alcohol solution and the 3-aminophenylboronic acid-modified sodium alginate solution is 5:20:15.

[0138] Comparative Example 4

[0139] The difference between this comparative example and Example 4 is only that:

[0140] In this comparative example, no borneol was added, and the gallic acid-modified polyvinyl alcohol was dissolved in distilled water.

[0141] Example 5

[0142] This embodiment provides a borneol analgesic burn repair hydrogel material. The difference between this embodiment and embodiment 1 is that:

[0143] In 1.3) of this embodiment, the mass of gallic acid powder is 0.4.

[0144] In 2.3) of this embodiment, the mass of methylmorpholine hydrochloride is 0.65 g.

[0145] In 3.1) of this embodiment, the mass of chitosan is 0.07 g.

[0146] In 3.4) of this embodiment, the concentration of the modified nano-borneol solution is 1.2 mg / mL.

[0147] In 4.4) of this embodiment, the volume ratio of the ZnSO4 solution, the gallic acid-modified polyvinyl alcohol solution and the 3-aminophenylboronic acid-modified sodium alginate solution is 15:20:30.

[0148] Comparative Example 5

[0149] The difference between this comparative example and Example 5 is only that:

[0150] In this comparative example, no borneol was added, and the gallic acid-modified polyvinyl alcohol was dissolved in distilled water.

[0151] Experimental Section

[0152] (I) Nuclear Magnetic Resonance Proton Spectrum Test

[0153] The present invention takes the gallic acid modified polyvinyl alcohol and 3-aminophenylboronic acid modified sodium alginate prepared in Example 1 as examples, and performs nuclear magnetic resonance hydrogen spectrum tests on them respectively, and the test results are as follows: Figure 2 shown.

[0154] Figure 2 Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the gallic acid-modified polyvinyl alcohol and the 3-aminophenylboronic acid-modified sodium alginate prepared in Example 1, wherein Figure A is the hydrogen nuclear magnetic resonance spectrum of the 3-aminophenylboronic acid-modified sodium alginate prepared in Example 1, and Figure B is the hydrogen nuclear magnetic resonance spectrum of the gallic acid-modified polyvinyl alcohol prepared in Example 1.

[0155] from Figure 2 As can be seen from Figure A, the new characteristic peak formed at 7.3ppm~7.7ppm comes from the chemical shift of the H atom on the benzene ring of 3-aminophenylboronic acid, indicating that 3-aminophenylboronic acid successfully modifies sodium alginate to obtain 3-aminophenylboronic acid modified sodium alginate.

[0156] from Figure 2 As can be seen from Figure B, the new characteristic peak formed at 6.5ppm~6.8ppm indicates that gallic acid has successfully modified polyvinyl alcohol to obtain gallic acid-modified polyvinyl alcohol.

[0157] (II) Self-healing performance test

[0158] The present invention takes PGSB of Example 1 and PGS of Comparative Example 1 as examples, and tests the self-healing performance thereof respectively. The specific method is to prepare disc-shaped PGSB and PGS hydrogels in advance. During the test, the PGSB and PGS hydrogels are first subjected to strain amplitude scanning by a rheometer to record the numerical changes of the storage modulus and loss modulus of the hydrogels. Subsequently, at a fixed angular frequency of 10 rad / s, a periodic alternating strain scanning test is performed on the PGSB and PGS hydrogels, and the strains are set to 1% and 1000% respectively, with a strain interval of 100s, and the scanning is repeated 3 times. The test results are shown in FIG. Figure 3 As shown, Figure 3 Where G' is the storage modulus of the hydrogel, and G" is the loss modulus of the hydrogel.

[0159] from Figure 3The test results show that at a low strain of 1%, both PGS and PGSB show a storage modulus > loss modulus, that is, they show a normal gel state. At a high strain of 1000%, both show a storage modulus < loss modulus, that is, they show a sol state. And in three repeated cycles, the storage modulus of PGS and PGSB can be restored to its initial value, which shows the excellent self-healing properties of PGS and PGSB hydrogels.

[0160] The present invention also takes the PGSB of Example 1 as an example, and cuts the original PGSB disc hydrogel of Example 1 into four pieces to further capture the macroscopic morphological changes of the self-healing behavior process, and conducts two sets of experiments in parallel, and records them as follows: Figure 4 shown.

[0161] from Figure 4 It can be observed that both groups of experiments showed the same phenomenon, that is, after the PGSB hydrogel of Example 1 was sliced ​​and put together, it would heal itself to its original shape, further verifying the self-healing property of the hydrogel from a macroscopic perspective.

[0162] (III) Adhesion performance test

[0163] The present invention takes the PGSB of Example 1 as an example and conducts an adhesion performance test on it. The test method is to evenly apply 100 μL of hydrogel to the surface of different substrates, and then attach it to a glass sheet. After standing at 25°C for 3 hours, the glass sheet is inverted to observe the adhesion of the hydrogel. The test results are respectively Figure 5 and Figure 6 shown.

[0164] in, Figure 5 Figures 2 show the adhesion test results of PGSB hydrogel to different substrates, where (a) shows the adhesion test results of PGSB hydrogel to 5mL glass bottle, (b) shows the adhesion test results of PGSB hydrogel to 20mL glass bottle, (c) shows the adhesion test results of PGSB hydrogel to 5mL plastic centrifuge tube, (d) shows the adhesion test results of PGSB hydrogel to 50mL plastic centrifuge tube, (e) shows the adhesion test results of PGSB hydrogel to 20g wood block, (f) shows the adhesion test results of PGSB hydrogel to 20g metal weight, and (g) shows the adhesion test results of PGSB hydrogel to 50g metal weight.

[0165] Depend on Figure 5 It can be seen from the tests that PGSB hydrogel has good adhesion to different substrates.

[0166] Figure 6Figures 2 and 3 show the adhesion test results of PGSB hydrogel to organic tissue substrates, wherein (a) shows the adhesion test results of PGSB hydrogel to mouse kidney, (b) shows the adhesion test results of PGSB hydrogel to mouse spleen, (c) shows the adhesion test results of PGSB hydrogel to mouse heart, (d) shows the adhesion test results of PGSB hydrogel to mouse liver, and (e) shows the adhesion test results of PGSB hydrogel to mouse lung.

[0167] Depend on Figure 6 The tests showed that PGSB hydrogel was able to adhere to organic tissue substrates including mouse kidney, mouse spleen, mouse heart, mouse liver and mouse lung, further proving that PGSB hydrogel has excellent adhesion properties.

[0168] (IV) Determination of in vitro cell compatibility

[0169] 1) Cell morphology observation and viability test

[0170] The present invention takes PGSB of Example 1 and PGS of Comparative Example 1 as examples, and performs cell morphology observation and vitality test after co-culture with cells. The test method is to inoculate L929 cells from the Chinese Academy of Sciences in a 96-well plate with 10% fetal bovine serum (containing antibiotics). After L929 cells adhere to the wall for 5 hours, the pre-prepared PGS and PGSB hydrogels are placed in the wells. After co-culture for 24 hours, the 96-well plate is then transferred to a humidified incubator and incubated for 4 hours. The culture solution is aspirated and transferred to a black 96-well plate, and the fluorescence intensity (λ 激发波长 =560nm,λ 发射波长 =600nm), and cells without hydrogel were set as control group (TCP). Cell activity was detected by Live / Dead staining and observation of cell morphology under an inverted fluorescence microscope. Within the specified culture time, the cell compatibility of PGS and PGSB was tested by live / dead assay and cell viability assay.

[0171] The test results are as follows Figure 7 As shown. Figure 7 The fluorescence microscopy morphology of L929 cells co-cultured with hydrogels for different days shows the morphology of L929 cells after 1 day and 5 days of co-culture with hydrogels. During the co-culture period, the cells all showed a green spindle shape, and no red dead cells were observed, indicating that the hydrogel was not toxic to the cells.

[0172] 2) Cell viability test

[0173] The present invention takes PGSB of Example 1 and PGS of Comparative Example 1 as examples, and performs cell viability tests on them respectively. The test results are as follows: Figure 8 shown.

[0174] Depend on Figure 8 It can be seen that after the first day of co-culture, the cells in the blank group seeded on the well plate showed similar viability to the PGS and PGSB hydrogel groups. As the culture time increased, the cell viability of the PGS and PGSB groups increased significantly compared with the blank group on the fifth day compared with the first day, showing a significant difference.

[0175] Cell proliferation and live / dead staining demonstrated that PGS and PGSB hydrogels had good cell compatibility.

[0176] (V) Antibacterial performance test

[0177] The present invention takes the PGSB of Example 1 and the PGS hydrogel of Comparative Example 1 as examples, and respectively conducts antibacterial performance tests on them. The test method is to drop the bacterial suspension onto the PGS or PGSB hydrogel, and then co-culture the bacteria and the hydrogel in an automatic shaker for 24 hours. Afterwards, a phosphate buffered saline solution, i.e., a PBS saline solution, is injected into the plate to dilute the bacterial suspension. The control group is the diluted bacterial suspension. The diluted bacterial suspension is collected and cultured on a plate for 24 hours. The results are photographed and the sterilization rate is calculated by the plate count method.

[0178] The test results are as follows Fig. 9 As shown, (a) is a schematic diagram of an Escherichia coli culture plate, and (b) is a schematic diagram of a Staphylococcus aureus culture plate.

[0179] Depend on Fig. 9 As can be observed in Figures (a) and (b), there are no colonies in the PGS and PGSB treatment groups. In contrast, the colonies in the control group filled the plate. This indicates that PGS and PGSB hydrogels have good bactericidal ability.

[0180] The present invention also tests the antibacterial rate of PGSB of Example 1 and PGS of Comparative Example 1, and the bactericidal rate of the hydrogel against bacteria is calculated by the following formula 1:

[0181] Sterilization rate (%) = (Nb-Na) / Nb×100% Formula 1;

[0182] In formula 1, Nb is the colony count of the control group; Na is the colony count of the sample group.

[0183] The test results are as follows Fig.10 and Fig.11 As shown, Fig.10 Schematic diagram of the antibacterial rate of PGS and PGSB hydrogels against Escherichia coli. Fig.11 Schematic diagram of the antibacterial rate of PGS and PGSB hydrogels against Staphylococcus aureus.

[0184] Depend on Fig.10and Fig.11 It can be seen that through the calculation of the antibacterial rates of PGS and PGSB hydrogels against Escherichia coli and Staphylococcus aureus, more than 99% of Escherichia coli and Staphylococcus aureus were eliminated, proving that PGS and PGSB hydrogels have excellent bactericidal ability.

[0185] (VI) In vivo healing test of burn wounds in mice infected with Staphylococcus aureus

[0186] The present invention takes the PGSB of Example 1 and the PGS hydrogel of Comparative Example 1 as examples to observe the healing effect on scald wounds infected with Staphylococcus aureus in mice. A hot steel rod with a diameter of 1 cm was placed on the back of the mouse to form a scald wound, and then Staphylococcus aureus was injected into the wound to form a scald wound infected with Staphylococcus aureus. Subsequently, the blank group was used as the control group, and the commercially available scald cream was used as the commercial control group. PGS and PGSB hydrogels were used to treat the infected scald wounds. The morphological repair changes of the infected scald wounds after treatment and the changes in the area of ​​the infected scald wounds were recorded as follows: Fig.12 and Fig.13 shown.

[0187] observe Fig.12 and Fig.13 It can be seen that on the third day, the wounds of mice were seriously infected. The wounds of the blank group expanded by 15.9%, the wounds of the scald ointment group shrank by 1.5%, and the wounds of the antibacterial PGS and PGSB hydrogel groups shrank by 21.1% and 60.4%, respectively. The healing effect of the PGSB hydrogel group was significantly improved compared with the PGS hydrogel group, indicating that the addition of borneol can significantly improve the scald repair effect of the hydrogel. And with the extension of the treatment time, after 7 days of treatment, the blank group and the scald ointment treatment group still had slight infection due to limited antibacterial activity, and the wound healing rates were 12.6% and 68.2%, respectively. The wound healing rates of the PGS hydrogel group and the PGSB hydrogel group were 74.0%, and the wound healing rates of the PGSB hydrogel group were 90.2%. After 14 days of treatment, the wound healing rates of the PGSB treatment group were 99.1%, the blank group wound healing rates were 39.6%, and the scald ointment treatment group wound healing rates were 85.9%. The above results show that PGSB hydrogel can treat burn wounds infected by Staphylococcus aureus, and the treatment effect is better than the burn ointment on the market, which proves that the PGSB hydrogel formed by adding borneol in the present invention has the effect of promoting the healing of infected burn wounds.

[0188] (VII) Analgesic effect of PGS and PGSB hydrogels in mice after scald

[0189] The present invention takes the PGSB of Example 1 and the PGS of Comparative Example 1 as examples, and records the facial expression index MGS of mice to evaluate the pain perception after scalding, such as Fig.14As shown. On the day after the scald, the MGS scores of all experimental groups were high; one day after the scald, the MGS scores of the commercial scald cream group, PGS group and PGSB group all decreased, among which the PGSB group decreased the most; in contrast, the blank group still showed a high MGS score; three days after the scald, the MGS scores of each group gradually decreased, and the MGS score of the PGSB treatment group was significantly lower than that of the other three groups due to its analgesic effect; after 5 days of treatment, except for the blank group mice with severe infection, the MGS scores of the scald cream and hydrogel groups mice decreased due to wound recovery. The results show that PGSB hydrogel has a good analgesic effect on infected scald wounds.

[0190] The hydrogel with multiple physical and chemical cross-linking effects loaded with nano-borneol prepared in the present invention has good self-healing performance, analgesia, biocompatibility, adhesion and antibacterial properties. In terms of self-healing performance, the hydrogel can automatically repair to its original state after breaking; in terms of analgesia, the hydrogel can effectively reduce the pain of mice; in terms of biocompatibility, the hydrogel has good cell compatibility, and the hemolysis rate is less than 5%; in terms of adhesion, the hydrogel can adhere to various substrates; in terms of antibacterial performance, the hydrogel has good bactericidal ability, and can kill more than 99% of Staphylococcus aureus and Escherichia coli. It lays a foundation for the application of hydrogel in the field of wound repair and has good application prospects.

[0191] Obviously, the above embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a borneol analgesic burn repair hydrogel material, characterized in that: The following steps are involved: In a protective gas atmosphere, under the action of a catalyst, gallic acid is grafted onto polyvinyl alcohol through an esterification reaction to obtain gallic acid-modified polyvinyl alcohol; In 2-morpholineethanesulfonic acid buffer, under the action of an activator, 3-aminophenylboronic acid is grafted onto sodium alginate through an amidation reaction to obtain 3-aminophenylboronic acid modified sodium alginate; The chitosan was coated on the surface of borneol by microemulsion method to obtain modified nano-borneol solution. dissolving the gallic acid-modified polyvinyl alcohol in the modified nano-borneol solution to obtain a gallic acid-modified polyvinyl alcohol solution; The 3-aminophenylboronic acid modified sodium alginate is dissolved in water to obtain a 3-aminophenylboronic acid modified sodium alginate solution; the gallic acid modified polyvinyl alcohol solution, the 3-aminophenylboronic acid modified sodium alginate solution and Zn 2+ The solution is mixed evenly to allow each component to fully contact and cross-link, thereby obtaining the borneol analgesic burn repair hydrogel material.

2. The preparation method according to claim 1, characterized in that The mass ratio of the gallic acid to the polyvinyl alcohol is 1 to 2:

1.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the 3-aminophenylboronic acid to sodium alginate is 0.6 to 1:

1.

4. The preparation method according to claim 1, characterized in that: The mass ratio of borneol to chitosan is 1:2-14.

5. The preparation method according to claim 1, characterized in that: The gallic acid modified polyvinyl alcohol solution, the 3-aminophenylboronic acid modified sodium alginate solution and the Zn 2+ The volume ratio of the solution is 1-2:3-10:1-3; The mass concentration of the modified nano-borneol solution is 0.8 mg / mL to 1.2 mg / mL; and the mass concentration of gallic acid-modified polyvinyl alcohol in the gallic acid-modified polyvinyl alcohol solution is 18 wt% to 22 wt%; The mass concentration of the 3-aminophenylboronic acid modified sodium alginate solution is 0.5wt% to 1wt%; The Zn 2+ The concentration of the solution is 0.08mol / L~0.12mol / L.

6. The preparation method according to claim 1, characterized in that: The catalyst is 4-dimethylaminopyridine; and the mass ratio of the catalyst to the polyvinyl alcohol is 5 to 8:

1.

7. The preparation method according to claim 1, characterized in that: The activator is one or more of methylmorpholine hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide; and the mass ratio of the activator to the 3-aminophenylboronic acid is 4 to 5:

1.

8. The preparation method according to claim 1, characterized in that: The reaction temperature of the esterification reaction is 65°C to 75°C, and the reaction time is 36h to 60h; The reaction temperature of the amidation reaction is room temperature, and the reaction time is 36h to 60h.

9. A borneol analgesic burn repair hydrogel material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the borneol analgesic burn repair hydrogel material according to any one of claim 9 in a burn wound repair dressing.